“A mini home far away from home.” The Thai temple and women’s sense of safety in Finland - Härkönen, Mitra (Frontiers in Psychology, 2024)
Introduction This article explores the significance of the Thai Buddhist temple for Thai women’s sense of safety in Finland. Despite the growing popularity of Buddhism in the country, research literature and media have largely ignored the religiosity of Thai women, focusing instead on negative stereotypes. The article highlights the importance of Buddhism and the temple in the lives of Thai women who have migrated to European countries and challenges biased portrayals of Thai women in previous research. Methods Based on ethnographic research at the Thai temples in Finland and life story interviews with twelve Thai women. Results The article argues that the temple plays a crucial role in promoting a sense of safety among Thai women by providing a sense of home, belonging, and meaning. The temple’s material and symbolic characteristics, in addition to its communality and relationality, work together to connect individuals with the temple’s religious significance, contributing to the women’s sense of security. Discussion These findings speak for the fact that when facing the challenges of Thai women or other religious and ethical minorities, it is necessary to also look to their religion as a source of mental and spiritual well-being.